IL-1-IL-17 Signaling Axis Contributes to Fibrosis and Inflammation in Two Different Murine Models of Systemic Sclerosis - Park, Min-Jung; Moon, Su-Jin; Lee, Eun-Jung; Jung, Kyung-Ah; Kim, Eun-Kyung; Kim, Da-Som; Lee, Jung-Ho; Kwok, Seung-Ki; Min, Jun-Ki; Park, Sung-Hwan; Cho, Mi-La (Frontiers in Immunology, 2018)
Objective: Systemic sclerosis (SSc) is a progressive fibrotic disease that affects the skin and internal organs. Despite evidence implicating increased interleukin-17 (IL-17) activity in SSc, the role of IL-17 in SSc remains uncertain. The purpose of this study was to investigate whether IL-17 plays a pathophysiological role in SSc in two different murine models of SSc. Methods: Bleomycin (BLM)-induced fibrosis and chronic graft-versus-host disease (cGVHD) models were used. Histological analysis was performed using Masson’s trichrome and immunohistochemical staining. Quantitative reverse transcription-polymerase chain reaction and enzyme-linked immunoassays were used to quantify the messenger RNA and protein levels of inflammatory mediators in dermal fibroblasts. Results: IL-1 receptor antagonist-deficient (IL-1Ra-KO) mice were more severely affected by BLM injection, as shown by dermal and pulmonary fibrosis, compared with wild-type (WT) mice. Increased tissue fibrosis was reversed by knocking down IL-17. In vitro experiments showed that IL-1 and IL-17 exerted synergistic effects on the expression of profibrotic and inflammatory mediators. In the cGVHD model, C57BL/6 mice receiving splenocytes of IL-1Ra-KO BALB/c mice developed more severe cGVHD than did those receiving cells from WT mice. Knockdown of IL-17 in IL-1Ra-KO donor mice significantly attenuated the IL-1-induced acceleration of cGVHD severity. Conclusion: Targeting IL-1 and its downstream IL-17 activity may be a novel treatment strategy for inhibiting inflammation and tissue fibrosis in SSc.